Kallikrein 12 Regulates Innate Resistance of Murine Macrophages against Mycobacterium bovis Infection by Modulating Autophagy and Apoptosis - Sabir, Naveed (Cells, 2019)
Mycobacterium bovis (M. bovis) is a member of the Mycobacterium tuberculosis (Mtb) complex causing bovine tuberculosis (TB) and imposing a high zoonotic threat to human health. Kallikreins (KLKs) belong to a subgroup of secreted serine proteases. As their role is established in various physiological and pathological processes, it is likely that KLKs expression may mediate a host immune response against the M. bovis infection. In the current study, we report in vivo and in vitro upregulation of KLK12 in the M. bovis infection. To define the role of KLK12 in immune response regulation of murine macrophages, we produced KLK12 knockdown bone marrow derived macrophages (BMDMs) by using siRNA transfection. Interestingly, the knockdown of KLK12 resulted in a significant downregulation of autophagy and apoptosis in M. bovis infected BMDMs. Furthermore, we demonstrated that this KLK12 mediated regulation of autophagy and apoptosis involves mTOR/AMPK/TSC2 and BAX/Bcl-2/Cytochrome c/Caspase 3 pathways, respectively. Similarly, inflammatory cytokines IL-1β, IL-6, IL-12 and TNF-α were significantly downregulated in KLK12 knockdown macrophages but the difference in IL-10 and IFN-β expression was non-significant. Taken together, these findings suggest that upregulation of KLK12 in M. bovis infected murine macrophages plays a substantial role in the protective immune response regulation by modulating autophagy, apoptosis and pro-inflammatory pathways. To our knowledge, this is the first report on expression and the role of KLK12 in the M. bovis infection and the data may contribute to a new paradigm for diagnosis and treatment of bovine TB.